B323 Comparison of ultrasound-guided erector spinae plane block and quadratus lumborum block for postoperative analgesia after caesarean section: a prospective randomised study. (11th August 2022) - Joshi, R; Jeevan, R; Amutha Selvaraju, V; Ramji Natarajan, N; Lakshmi, R
Abstract : Background and Aims: Caesarean section can cause somatic and visceral pain. Adding a regional anesthesia technique to multimodal analgesia improves the quality of postoperative pain relief. Quadratus lumborum block (QLB) has shown to provide good analgesia post-caesarean section. In this novel study, we aimed to compare Erector spinae plane block (ESPB) with QLB for analgesia after caesarean section. Methods: This prospective, randomized, double-blinded study was approved by the Institute ethics committee and registered with clinical trials registry (CTRI/2022/02/040404). Following exclusion, 112 patients were randomised to receive either a bilateral transmuscular QLB or an ESPB (at T12) with 20 ml 0.25% ropivacaine on each side (after the completion of caesarean section under subarachnoid block). All patients received prophylactic acetaminophen for 2 days.Our primary objective was to evaluate tramadol consumption in the first 48 hours. Secondary objectives were to compare the time for first rescue analgesic requirement, visual analogue scale (VAS) at rest and movement, to assess for any complication and to compare the overall satisfaction with analgesia. Results: The mean tramadol consumption at 48 hours, the duration of first rescue analgesia and patient satisfaction was similar between both the groups. NRS score was lower in ESPB on movement at 4 hours, at rest and movement at 6 hours and on movement at 36 hours, however, both groups had comparable NRS scores at other times. Neither group reported complications related to block ( Table 1 ). Conclusions: Bilateral ultrasound guided ESPB leads to an analgesic efficacy similar to bilateral Transmuscular QLB in patients undergoing caesarean section.